Creating sanctioning norms in the lab: the influence of descriptive norms in third-party punishment. (3rd April 2019) - Lois, Giannis; Wessa, Michèle
ABSTRACT: Third-party punishment is a form of peer-to-peer sanctioning that is influenced by descriptive norms. The present study aims to investigate how aggregate peer punishment and the presence of a free rider who never punishes influences the formation of third-party punishment norms. Participants were exposed to social feedback indicating either low, high, or high & free rider peer punishment. Over time, participants conformed to average peer punishment leading to the emergence and persistence of different sanctioning norms in each group. The presence of one free rider significantly reduced the average punishment and increased the frequency of free riding behavior. These findings highlight the critical role of descriptive norms and suggest the presence of a 'bad apple' effect in third-party punishment.